Organizational Commitment Profiles and Turnover Intention: Using a Person-Centered Approach in the Korean Context - Oh, Hyun Sung (Frontiers in Psychology, 2019)
Extensive research on organizational commitment profiles has been conducted as researchers recognized that individuals can concurrently experience various levels of organizational commitment. Although there is a growing body of research on commitment profiles within the past decade, existing empirical research has focused on Western cultural contexts and paid little attention to commitment profiles arising in Asian cultural contexts. The present study utilized a person-centered analytic method (latent profile analysis) to examine the types of commitment profiles among a sample of employees from South Korea (n = 510). From the results emerged six distinct commitment profiles of S. Korean employees, and these six profiles exemplified the differing impact of commitment profiles on turnover intentions. Finally, the implications of these results for commitment theory, practice and future research are discussed.